Find the locus of the point \[P\left( h,k \right)\] if three normals drawn from the
point \[P\] to
\[{{y}^{2}}=4ax\], satisfying the following \[{{m}_{1}}+{{m}_{2}}=1\].
Answer
Verified
512.7k+ views
Hint: Sum of slopes of three normals of parabola from a particular point is zero.
We are given a parabola \[{{y}^{2}}=4ax\] and point \[P\left( h,k \right)\] from which three
normals are drawn. Also, given that \[{{m}_{1}}+{{m}_{2}}=1\] that is the sum of slopes of two out of three normals is \[1\].
Now, we have to find the locus of point\[P\left( h,k \right)\].
We know that any general point on parabola \[{{y}^{2}}=4ax\] is \[\left( x,y \right)=\left( a{{t}^{2}},2at
\right)\].
We know that any line passing from \[\left( {{x}_{1}},{{y}_{1}} \right)\] and slope \[m\] is:
\[\left( y-{{y}_{1}} \right)=m\left( x-{{x}_{1}} \right)\].
So, the equation of normal at point \[\left( a{{t}^{2}},2at \right)\] and slope \[m\] is:
\[\left( y-2at \right)=m\left( x-a{{t}^{2}} \right)....\left( i \right)\]
Now we take the parabola, \[{{y}^{2}}=4ax\].
Now we differentiate the parabola.
\[\left[ \text{Also, }\dfrac{d\left( {{x}^{n}} \right)}{dx}=n{{x}^{n-1}} \right]\]
Therefore, we get \[2y\dfrac{dy}{dx}=4a\]
\[\dfrac{dy}{dx}=\dfrac{2a}{y}\]
At \[\left( x,y \right)=\left[ a{{t}^{2}},2at \right]\]
We get, \[\Rightarrow \dfrac{dy}{dx}=\dfrac{2a}{2at}=\dfrac{1}{t}\]
As \[\dfrac{dy}{dx}\] signify the slope of tangent, therefore any tangent on parabola at point
\[\left(
a{{t}^{2}},2at \right)\] would have slope \[=\dfrac{1}{t}\].
Now, we know that tangent and normal are perpendicular to each other.
Therefore, \[\left( \text{Slope of tangent} \right)\times \left( \text{Slope of normal} \right)=-1\]
As we have found that \[\text{Slope of tangent =}\dfrac{1}{t}\] and assumed that slope of normal is \[m\].
Therefore, we get \[\left( \dfrac{1}{t} \right)\times \left( m \right)=-1\].
Hence, \[t=-m\]
Putting value of \[t\]in equation \[\left( i \right)\],
We get, \[\left[ y-2a\left( -m \right) \right]=m\left[ x-a{{\left( -m \right)}^{2}} \right]\]
\[\Rightarrow y+2am=m\left( x-a{{m}^{2}} \right)\]
\[\Rightarrow y=mx-a{{m}^{3}}-2am\]
By rearranging the given equation,
We get, \[a{{m}^{3}}+m\left( 2a-x \right)+y=0\]
Here, we get three degree equation in terms of \[m\], therefore it will have \[3\] roots
\[{{m}_{1}}, {{m}_{2}}\] and \[{{m}_{3}}\].
As we know that this normal passes through \[\left( h,k \right)\], we put \[x=h\] and \[y=k\].
We get, \[a{{m}^{3}}+m\left( 2a-h \right)+k=0....\left( ii \right)\]
Comparing above equation by general three degree equation \[a{{x}^{3}}+b{{x}^{2}}+cx+d=0\]
We get, \[a=a,\text{ }b=0,\text{ }c=\left( 2a-h \right),\text{ }d=k\]
We know that \[\text{sum of roots }=\dfrac{-b}{a}\]
As \[b=0\] in equation \[\left( ii \right)\],
Therefore, we get \[\text{sum of roots }=0\].
As \[{{m}_{1}}, {{m}_{2}}\] and \[{{m}_{3}}\] are roots,
Hence, \[{{m}_{1}}+{{m}_{2}}+{{m}_{3}}=0\]
As we have been given that \[{{m}_{1}}+{{m}_{2}}=1\],
We get \[1+{{m}_{3}}=0\]
Therefore, \[{{m}_{3}}=-1\]
As \[{{m}_{3}}\] is root of equation \[\left( ii \right)\],
Therefore, it will satisfy the equation \[\left( ii \right)\].
Now, we put \[{{m}_{3}}\] in equation \[\left( ii \right)\],
We get \[a{{\left( {{m}_{3}} \right)}^{3}}+{{m}_{3}}\left( 2a-h \right)+k=0\]
As, \[{{m}_{3}}=-1\]
We get, \[a{{\left( -1 \right)}^{3}}+\left( -1 \right)\left( 2a-h \right)+k=0\]
\[\Rightarrow -a-\left( 2a-h \right)+k=0\]
\[\Rightarrow -3a+h+k=0\]
\[h+k=3a\]
Now, to get the locus of \[\left( h,k \right)\], we will replace \[h\] by \[x\] and \[k\] by \[y\].
So, we get \[x+y=3a\]
Hence, we get locus of point \[P\left( h,k \right)\Rightarrow \left( x+y \right)=3a\]
Note: Mistake could be committed in writing the value of sum of roots \[=\dfrac{-b}{a}\] as in
hurry,
students often write coefficient of second term as \[b\]that is they write \[b=\left( 2a-h \right)\] but
actually \[b\] is the coefficient of \[{{m}^{2}}\] which is zero in the given question.
We are given a parabola \[{{y}^{2}}=4ax\] and point \[P\left( h,k \right)\] from which three
normals are drawn. Also, given that \[{{m}_{1}}+{{m}_{2}}=1\] that is the sum of slopes of two out of three normals is \[1\].
Now, we have to find the locus of point\[P\left( h,k \right)\].
We know that any general point on parabola \[{{y}^{2}}=4ax\] is \[\left( x,y \right)=\left( a{{t}^{2}},2at
\right)\].
We know that any line passing from \[\left( {{x}_{1}},{{y}_{1}} \right)\] and slope \[m\] is:
\[\left( y-{{y}_{1}} \right)=m\left( x-{{x}_{1}} \right)\].
So, the equation of normal at point \[\left( a{{t}^{2}},2at \right)\] and slope \[m\] is:
\[\left( y-2at \right)=m\left( x-a{{t}^{2}} \right)....\left( i \right)\]
Now we take the parabola, \[{{y}^{2}}=4ax\].
Now we differentiate the parabola.
\[\left[ \text{Also, }\dfrac{d\left( {{x}^{n}} \right)}{dx}=n{{x}^{n-1}} \right]\]
Therefore, we get \[2y\dfrac{dy}{dx}=4a\]
\[\dfrac{dy}{dx}=\dfrac{2a}{y}\]
At \[\left( x,y \right)=\left[ a{{t}^{2}},2at \right]\]
We get, \[\Rightarrow \dfrac{dy}{dx}=\dfrac{2a}{2at}=\dfrac{1}{t}\]
As \[\dfrac{dy}{dx}\] signify the slope of tangent, therefore any tangent on parabola at point
\[\left(
a{{t}^{2}},2at \right)\] would have slope \[=\dfrac{1}{t}\].
Now, we know that tangent and normal are perpendicular to each other.
Therefore, \[\left( \text{Slope of tangent} \right)\times \left( \text{Slope of normal} \right)=-1\]
As we have found that \[\text{Slope of tangent =}\dfrac{1}{t}\] and assumed that slope of normal is \[m\].
Therefore, we get \[\left( \dfrac{1}{t} \right)\times \left( m \right)=-1\].
Hence, \[t=-m\]
Putting value of \[t\]in equation \[\left( i \right)\],
We get, \[\left[ y-2a\left( -m \right) \right]=m\left[ x-a{{\left( -m \right)}^{2}} \right]\]
\[\Rightarrow y+2am=m\left( x-a{{m}^{2}} \right)\]
\[\Rightarrow y=mx-a{{m}^{3}}-2am\]
By rearranging the given equation,
We get, \[a{{m}^{3}}+m\left( 2a-x \right)+y=0\]
Here, we get three degree equation in terms of \[m\], therefore it will have \[3\] roots
\[{{m}_{1}}, {{m}_{2}}\] and \[{{m}_{3}}\].
As we know that this normal passes through \[\left( h,k \right)\], we put \[x=h\] and \[y=k\].
We get, \[a{{m}^{3}}+m\left( 2a-h \right)+k=0....\left( ii \right)\]
Comparing above equation by general three degree equation \[a{{x}^{3}}+b{{x}^{2}}+cx+d=0\]
We get, \[a=a,\text{ }b=0,\text{ }c=\left( 2a-h \right),\text{ }d=k\]
We know that \[\text{sum of roots }=\dfrac{-b}{a}\]
As \[b=0\] in equation \[\left( ii \right)\],
Therefore, we get \[\text{sum of roots }=0\].
As \[{{m}_{1}}, {{m}_{2}}\] and \[{{m}_{3}}\] are roots,
Hence, \[{{m}_{1}}+{{m}_{2}}+{{m}_{3}}=0\]
As we have been given that \[{{m}_{1}}+{{m}_{2}}=1\],
We get \[1+{{m}_{3}}=0\]
Therefore, \[{{m}_{3}}=-1\]
As \[{{m}_{3}}\] is root of equation \[\left( ii \right)\],
Therefore, it will satisfy the equation \[\left( ii \right)\].
Now, we put \[{{m}_{3}}\] in equation \[\left( ii \right)\],
We get \[a{{\left( {{m}_{3}} \right)}^{3}}+{{m}_{3}}\left( 2a-h \right)+k=0\]
As, \[{{m}_{3}}=-1\]
We get, \[a{{\left( -1 \right)}^{3}}+\left( -1 \right)\left( 2a-h \right)+k=0\]
\[\Rightarrow -a-\left( 2a-h \right)+k=0\]
\[\Rightarrow -3a+h+k=0\]
\[h+k=3a\]
Now, to get the locus of \[\left( h,k \right)\], we will replace \[h\] by \[x\] and \[k\] by \[y\].
So, we get \[x+y=3a\]
Hence, we get locus of point \[P\left( h,k \right)\Rightarrow \left( x+y \right)=3a\]
Note: Mistake could be committed in writing the value of sum of roots \[=\dfrac{-b}{a}\] as in
hurry,
students often write coefficient of second term as \[b\]that is they write \[b=\left( 2a-h \right)\] but
actually \[b\] is the coefficient of \[{{m}^{2}}\] which is zero in the given question.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE